The development of a preservation framework for primary research data and records for research in digital formats - Mohd Yunus, Alwi (2017)
This study is an attempt to gain greater understanding of the preservation of primary data and records of social science research in digital formats. The work draws from the perceptions and ideas of those involved in the management and preservation of these records namely the researchers, research administrators, records managers and IT officers at the public research institutions and related organizations. Essentially mix-method in nature, this study sampled 411 respondents from eleven research institutions and related organizations for quantitative data and twelve informants for qualitative data from individual interviews and focus group discussions to permit purposive sampling. Qualitative data was also elicited from documents analysis. Phase one of the studyinvolved the examination and analysis of international best practice models and developed a generic model based on the InterPARES Chain of Preservation (CoP) and the United Kingdom Data Archives (UKDA) models.